Study of demographic features in retropositive pregnant women - A., Saravana; Patil, Shashikala B.; Rashmi, K. S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Study of demographic features like age, educational status of the patient and her husband, occupation of the patient and her husband and religion of the retropositive pregnant women compared to controls. Methods: In this prospective study patients were selected from Vani Vilas Hospital attached to Bangalore Medical College attending the antenatal Clinic of Obstetrics and Gynaecology. The study period was for 2 years. The study group comprised of 100 HIV seropositive patients. The control group comprised of 100 HIV seronegative patients. At enrollment, data collection of demographic features like age, educational status of the patient and her husband, occupation of patient and her husband, and religion of the retropositive pregnant women compared to controls. Results: The minimum and maximum age in the study group was 18 and 36 years respectively and in the control group 17 and 35 years respectively. Around 73% of pregnant women in the study group were below 25 years of age. 89% of pregnant women in the study group were Hindus. Around 36% of women in the study group were illiterate compared to 21% in the control group. Around 45% of women in the control group have studied till secondary school. In this study, most of the women in both the groups were housewives. There was one commercial sex worker and 8 women had polygamous relationship in the study group. The occupational pattern of the husbands was analyzed and 34% of the husbands of HIV positive women were drivers. 56% of the husbands in the study group admitted to have had multiple sexual partners, whereas only 9% admitted so, in the control group. Conclusions: Retropositive pregnant women were younger; most of them were house wives. Husbands of retropositive pregnant women were drivers and most of them had multiple sexual partners.